Evaluasi Material dan Daya Dukung Tanah untuk Base Coarse Jalan Tambang di PT. Kalimantan Prima Persada SiteMining Asam – asam (MASS) - Tommy Joetra; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
Abstrak. PT Kalimantan Prima Persada (PT. KPP) is a subsidiary of PT Pamapersada Nusantara which was established on September 9th, 2003. The company uses open pit method, the hauling overburden process uses 4 fleet with overburden (OB) production target of 40,000 BCM / day. In mine road maintenance the company does not yet have a reference for the selection of materials used for the base coarse of the mine road. The company uses the largest transport equipment, HD 785 which has a load of 529.33 kN / set, the CBR value of the road that can support the load is 36%, but the actual field found in the mine road CBR value ranges from 20% - 30% which can cause damage such as the occurrence of deflection, hollow roads and bumpy roads, so that it can increase the circulation time of the transport equipment and automatically reduce the productivity of the conveyances. Overburden's production target for 1 fleet is 10,000 BCM /day, but due to damage to the actual Anthea road in the production field for 1 fleet it does not meet the target.From the Dynamic Cone Penetrometer (DCP) test conducted on Anthea road using rover 1 and rover 2 material, the average CBR was 43.2%, while on the Gotik road using rover 3 material, the CBR average was 25%. Based on the calculation before the repairs on the Anthea road, the circulation time of 978.1 seconds was obtained, Overbuden production was 9,734 BCM /day.After the soak test, the material that can be used for the base coarse of the mine road is obtained, namely lower material 2, Rover 1 and rover 2 and mine road repairs with the addition of base coarse thickness, road compaction and scrubbing obtained decline in transport time to 910.5 seconds so overburden production increases to 10,457.41 BCM /dayKeywords :Base Coarse, CBR, DCP, Productivity, Production